The archaeology of culturally modified trees: Indigenous economic diversification within colonial intercultural settings in Cape York Peninsula, northeastern Australia. (May 2013) - Morrison, Mick; Shepard, Emily
Abstract : Developing holistic accounts of indigenous peoples' lifeways in colonial intercultural settings requires data that provide insights into patterns of landscape use and variations in social, economic, and cultural practices away from nodes of colonial activity. However, the mobile settlement patterns of some indigenous peoples mean that the data necessary for such investigations can be rare. In western Cape York Peninsula of northeastern Australia, culturally modified trees (CMTs) associated with the collection of wild honey or "sugarbag" provide opportunities to investigate indigenous patterns of landscape use and processes of economic change within colonial settings. Here we use CMT data to suggest that increased engagement with invader-settlers resulted in intensification of indigenous wild food production. This study exemplifies the complexity of socioeconomic shifts that accompanied European colonization worldwide, and illustrates how landscape-level data can provide information on the broader histories of indigenous peoples within colonial settings.